2020
DOI: 10.1093/mnras/staa513
|View full text |Cite
|
Sign up to set email alerts
|

WISE mid-infrared properties of compact active galactic nuclei selected from the high radio frequency AT20G survey

Abstract: Past studies of compact active galactic nuclei (AGNs), the dominant population at high radio frequencies, selected them using flat spectral index criteria. This biases the sample due to the steepening of AGN spectra at high radio frequencies. We improve upon this by selecting 3610 compact AGNs using their angular size information (∼0.15 arcsec scale) from the Australia Telescope 20 GHz (AT20G) high-angular-resolution catalogue. We cross-match these against the Wide-field Infrared Survey Explorer All-WISE catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Very few FRI/II and GPS/CSS sources have WISE colors as red as our sample. A similar result was seen by Chhetri et al (2020), who found that compact radio AGN have bluer WISE colors than AGN selected by optical/IR techniques. Thus, although our sample was pre-selected to have very red WISE colors, other classes of object with similarly compact radio sources (CCS/GPS/HFP) do not share these MIR colors.…”
Section: Wise Colors Of Compact Radio Agnsupporting
confidence: 84%
“…Very few FRI/II and GPS/CSS sources have WISE colors as red as our sample. A similar result was seen by Chhetri et al (2020), who found that compact radio AGN have bluer WISE colors than AGN selected by optical/IR techniques. Thus, although our sample was pre-selected to have very red WISE colors, other classes of object with similarly compact radio sources (CCS/GPS/HFP) do not share these MIR colors.…”
Section: Wise Colors Of Compact Radio Agnsupporting
confidence: 84%
“…Mid-infrared colour-colour plots are commonly used as a diagnostic tool for radiatively efficient AGN activity and sample selections (see e.g. Donley et al 2012 ;Mateos et al 2012 ;Stern et al 2012 ;Assef et al 2013 ;Secrest et al 2015 ;Chhetri et al 2020 ), though their usefulness for selecting AGN is limited to very bright radiatively efficient sources (quasars and bright Seyfert galaxies), where the torus component dominates, and often fainter AGN are missed (see e.g. G ürkan, Hardcastle & Jarvis 2014 ;Rovilos et al 2014 ;Mingo et al 2016 ;G ürkan et al 2018Retana-Montenegro & R öttgering 2020 ).…”
Section: Mid-ir Diagnosticsmentioning
confidence: 99%
“…Many of these radio sources seem to be young or unlikely to grow to large sizes, so it is yet unclear how they tie in with the evolved FRI/II classes, and what impact they might have beyond their host galaxies (e.g. Chhetri et al 2020 ;Patil et al 2020 ). We are also achieving greater insight on the bright compact steep spectrum and gigahertz peaked spectrum populations, with radio powers comparable to those of extended radio galaxies, but which are far too numerous to always evolve into FRIs and FRIIs (see e.g.…”
mentioning
confidence: 99%
“…Mid-infrared colour-colour plots are commonly used as a diagnostic tool for radiatively efficient AGN activity and sample selections (see e.g. Mateos et al 2012;Stern et al 2012;Donley et al 2012;Assef et al 2013;Secrest et al 2015;Chhetri et al 2020), though their usefulness for selecting AGN is limited to very bright radiatively efficient sources (quasars and bright Seyfert galaxies), where the torus component dominates, and often fainter AGN are missed (see e.g. Rovilos et al 2014;Gürkan et al 2014Gürkan et al , 2018Gürkan et al , 2019Mingo et al 2016;Retana-Montenegro & Röttgering 2020).…”
Section: Mid-ir Diagnosticsmentioning
confidence: 99%
“…Many of these radio sources seem to be young or unlikely to grow to large sizes, so it is yet unclear how they tie in with the evolved FRI/II classes, and what impact they might have beyond their host galaxies (e.g. Chhetri et al 2020;Patil et al 2020). We are also achieving greater insight on the bright compact steep spectrum (CSS) and gigahertz peaked spectrum (GPS) populations, with radio powers comparable to those of extended radio galaxies, but which are far too numerous to always evolve into FRIs and FRIIs (see e.g.…”
Section: Introductionmentioning
confidence: 99%